Marine Resource Damage Assessment Liability and Compensation for Environmental Damage - Maes, F. (Springer Netherlands : Imprint: Springer, 2005)
Prof. Dr. FRANK MAES Department of Public International Law & Maritime Institute Ghent University, Belgium Universiteitstraat 6, B - Ghent, Tel. : + 32 9 264 68 95, Fax: + 32 9 264 69 89 E-mail: Frank. Maes@UGent. be The contributions to this book are partly the output of a research project conducted between 1998 and 2002 in Belgium and a conference held at the Ghent University, Belgium, in June 2003 on the topic "Marine Resource Damage Assessment and Compensation for Environmental Damage" (MARE-DASM). The Belgian Federal Science Policy sponsored both the research and the conference. MARE-DASM research focused on: (i) the estimation and distribution of marine contaminants in order to assess their long term effects (ecotoxicology); (ii) the integration of these result into a Biological Effects SubModel and a mathematical model assessing the risks associated with accidental spillage of oil at sea and the damage this can cause (modelling); (iii) the assessment of the willingness to pay for ecological damage, based on the Contingent Valuation Method (economics); (iv) the development and evaluation of measures to be taken in order to guarantee a sustainable use of the Belgian part of the North Sea, taking into account the economic and social interests and values (social economics); (v) the potential to develop technical and legal procedures that allow ecological damage to the marine environment to be evaluated and compensated, taking into account constraints in national and international liability legislation (legal).